Occlusal Analysis of Algorithm-designed Restoration Using Different Virtual Articulator Parameters: A Preliminary Study - Shan-lin Guo; Xiao He; Zhi Tang; Bing-ying Xie; Min-jie Mao; Xiao-qing Shen; Yuan-ming Geng; Wei Li (International Dental Journal, 2025)
Introduction and aims: To investigate how different virtual articulator parameter settings influence clinical outcomes of posterior CAD/CAM restorations designed with the CEREC system's biogeneric model, specifically regarding occlusal rehabilitation. Methods: Twenty participants (11 females, 9 males; mean age 35.50 ± 5.23 years) each received four crowns designed under one of four protocols: (1) No Virtual Articulator Parameters (NVAP), (2) Mean Virtual Articulator Parameters (MVAP), (3) Partially Personalised Virtual Articulator Parameters (PPVAP), and (4) Fully Personalised Virtual Articulator Parameters (FPVAP). Subjective comfort was assessed via the Visual Analogue Scale and Likert scale. Intraoral scans were analysed using Geomagic Control X 2020 software to assess occlusal contact areas and points at single-tooth and full-arch levels. One-year restoration survival was not recorded. Results: MVAP and FPVAP showed significantly lower Visual Analogue Scale scores than NVAP (P = .0084, P = .0002, respectively). Likert scale ratings did not differ among groups (P = .9921). All crown designs reduced occlusal contact areas compared to the pre-preparation state (P < .05), with FPVAP exhibiting the most favorable outcomes, though not significantly different from other designs. Full-arch analysis revealed no significant changes in contact areas (P = .2645) or contact points (P = .5015). Two NVAP restorations fractured within one year (P = .0348), indicating a trend favoring increased parameter personalization. Conclusions: Mean-value or fully personalised virtual articulator parameters in CAD/CAM crown design yield superior patient comfort and maintain more accurate occlusal relationships compared to non-personalised approaches. Mean-value settings present a practical option for general clinical use, although larger-scale studies with extended follow-up are recommended. Clinical relevance: By integrating mean-value or fully personalised virtual articulator parameters into CAD/CAM restoration workflows, clinicians can significantly enhance patient comfort and occlusal accuracy. These findings highlight the importance of tailoring design parameters in routine practice to improve restoration outcomes and potentially lower the likelihood of failure.